+0

# https://vle.mathswatch.co.uk/images/questions/question512.png

+1
165
2
+348

https://vle.mathswatch.co.uk/images/questions/question512.png

really need help

ask CPhill i liked his posts.

lynx7  Nov 18, 2017
edited by lynx7  Nov 18, 2017
Sort:

#1
+6536
+3

Rearrange  w  =  3(2a + b ) - 4  to make  a  the subject.

w  =  3(2a + b) - 4

Add  4  to both sides of the equation.

w + 4  =  3(2a + b)

Divide both sides of the equation by  3 .

(w + 4)/3  =  2a + b

Subtract  b  from both sides.

(w + 4)/3 - b  =  2a

Divide both sides by  2 .

[ (w + 4)/3 - b ] / 2  =  a

a  =  [ (w + 4)/3 - b ] / 2

hectictar  Nov 18, 2017
#2
+4

Solve for a:
w = 3 (2 a + b) - 4

w = 3 (2 a + b) - 4 is equivalent to 3 (2 a + b) - 4 = w:
3 (2 a + b) - 4 = w

Expand out terms of the left hand side:
-4 + 6 a + 3 b = w

Subtract 3 b - 4 from both sides:
6 a = 4 - 3 b + w

Divide both sides by 6:
a = 2/3 - b/2 + w/6

Guest Nov 18, 2017

### 25 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details